Sensory World - Introduction to Sensation and Perception - Bennett,tl - Fineman, MB (Contemporary Psychology, 1979)
tex.unique-id: ISI:A1979HH96300043
Keywords: dept.psy; ⛔ No DOI found

Premorbid Social Competence and Outcome among Schizophrenic and Nonschizophrenic Patients - Zigler, Edward; Glick, Marion; Marsh, Anna (The Journal of Nervous and Mental Disease, 1979)
The relation between premorbid social competence and outcome was examined with 381 male state hospital patients in four diagnostic categories: schizophrenia, affective reaction, psychoneurotic disorder, and personality disorder. Outcome was assessed using the measures of length of initial hospitaliz
26 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1979HL47900004 tex.unique-id: [object Object]
Keywords: Affective Symptoms; Hospitals; Psychiatric; Human; Length of Stay; Male; Neurotic Disorders; Outcome and Process Assessment (Health Care); Personality Disorders; Prognosis; Schizophrenia; Schizophrenic Psychology; Social Adjustment; Support; U.S. Gov't; P.H.S.; affective neurosis; central nervous system; dept.psy; hospitalization; major clinical study; neurosis; personality disorder; schizophrenia; sociology; therapy